2019
DOI: 10.2139/ssrn.3456633
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Criminalisation of the Payment for Sexual Services in Northern Ireland

Abstract: The report is undoubtedly more relevant in policy terms because of their input. Thanks also to the support workers from the Belfast Commercial Sex Workers Service who provided information on the on-street sector in Belfast and to the Sex Workers Alliance Ireland and UglyMugs.ie who provided advice on the project as well as assisting in the distribution of the questionnaire and dealing with queries from sex workers about it. Special thanks also to Uglymugs.ie for providing data in relation to violence and abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Physical assaults and sexual violence were reported at lower levels, but still at higher rates than the general population. Ellison et al (2019) carried out an online survey of n ¼ 199 sex workers working in NI, none of whom identified as street sex workers, reflecting the Northern Irish sex work population which is 'almost exclusively based online ' (p. 38). They found that amongst those respondents who said they had been victimised while doing sex work in NI, the most common offence categories in order of prevalence were abusive or threatening phone calls/messages (73.3% of sex workers in their survey reported receiving these in the previous 12 months), in-person threatening or abusive behaviour (50.6% said they had experienced such in the previous 1 months), assault, robbery and rape/sexual assault.…”
Section: Prevalence and Nature Of Sex Work Victimisationmentioning
confidence: 99%
See 4 more Smart Citations
“…Physical assaults and sexual violence were reported at lower levels, but still at higher rates than the general population. Ellison et al (2019) carried out an online survey of n ¼ 199 sex workers working in NI, none of whom identified as street sex workers, reflecting the Northern Irish sex work population which is 'almost exclusively based online ' (p. 38). They found that amongst those respondents who said they had been victimised while doing sex work in NI, the most common offence categories in order of prevalence were abusive or threatening phone calls/messages (73.3% of sex workers in their survey reported receiving these in the previous 12 months), in-person threatening or abusive behaviour (50.6% said they had experienced such in the previous 1 months), assault, robbery and rape/sexual assault.…”
Section: Prevalence and Nature Of Sex Work Victimisationmentioning
confidence: 99%
“…For indoor workers who previously would not go to buyers' homes or other outcall locations, they are now under increased pressure to do so to avoid detection by the police or eviction from their own homes (Amnesty International, 2016). Ellison et al (2019) funded by Northern Ireland Department of Justice reviewed the impact of law to criminalise purchasing sexual services which came into law in 2015. Reviewing research studies which have looked at the impact of sex purchase legislation on risk and victimisation, they accepted as a general point that such law increases violence and abuse.…”
Section: Prevalence and Nature Of Sex Work Victimisationmentioning
confidence: 99%
See 3 more Smart Citations